Vocational Teacher Education in Central Asia: Developing Skills and Facilitating Success - Drummer, Jens; Hakimov, Gafurjon; Joldoshov, Mamatair; Köhler, Thomas; Udartseva, Svetlana (Technical and Vocational Education and Training: Issues, Concerns and Prospects, 2018)
teacher training; project based learning; educational technology; research methodology; network development; vocational teacher education; developing teaching skills; technical teacher education; Central Asia; GIZ Programme Professional Education in Central Asia; PBL; TVET; USPECH; Kazakhstan; Kyrgyzstan; Tajikistan; vocational education